RESPONSABILIDAD SOCIAL EMPRESARIAL Y DESARROLLO LOCAL EN LA MINERÍA AURÍFERA: EL CASO PIERINA (ANCASH) - López Mas, Julio (2005)
Through the visits to the areas, observations and interviews with the commoners and local authorities where the mine operates, it is verified that after more than five years of mining operations, there is a low acceptance of this mining company, though conflicts don´t exist. Although it is certain that the enterprise carries out programs related to environmental sustainability : erosion control, prevention and treatment of slipping lands, study of systems of waters and the use of land. This results quite unsatisfactory because the social and economic development is limited, programs of investment are few, employment is scarce and temporal, there are no local purchases and the effect of contamination is growing in these local communities. Piloting activities are being given with the purpose of promoting cattle (alpaca breeding) and agriculture as well as technical assistance and training with the intention of encouraging new investments in this region of our country.